Students' Pedagogic Literacy Skills Based on Textbook Development Teaching Strategies in Biology - Hasruddin Hasruddin; Aryeni Aryeni; Salwa Rezeqi; Adi Hartono (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study was to evaluate the pedagogical literacy skills of biology education students after studying lecture material from textbooks on biology teaching and learning strategies that have been developed based on the ADDIE model. This development research used 92 students of the Biology Education Study Program, FMIPA, State University of Medan as subjects, who were determined by random sampling technique. Pedagogic literacy is measured using an essay test to determine the ability of prospective teacher students according to developments in technology and communication. The data were analyzed by percentage technique. The results of the study found that students' pedagogic literacy abilities in preparing themselves for e-learning were included in the good category (82.45%), the use of digital learning in the very good category (91.84%), the learning components involved in online learning is included in the very good category (92.67%), and the use of authentic assessment is included in the good category (84.78%).